Determination of Optimum Mud Weight Window for Tanuma Formation in Southern Iraq (Journal of Engineering, 2024)
Problems with borehole instability contribute to an increase in non-productive time, mostly when drilling shale rocks. Drilling in this layer has several issues, including mud loss, tight holes, mechanically stuck pipes, caving, and large holes collapsing. The purpose of this paper is to construct a mechanical earth model (MEM) to evaluate the wellbore's stability. Through the application of MEM, the paper is focused on determining a range of mud weights that would ensure safety and optimize the drilling operation of new wells. The study of wellbore instability indicated that the main factor contributing to these complications was inadequate mud weight during the drilling process in the Tanuma shale formation. Moreover, as the wellbore inclination changed, the quantity of drilling density necessary to penetrate the Tanuma formation also changed substantially. In the Tanuma formation, wellbore angles surpassing 20° should be avoided, according to the model. The model issue that primarily refers to the shear failure in the Tanuma formation was comparatively reduced in the NW-SE direction (in the direction of the minimum horizontal stress). Furthermore, the sensitivity analysis showed that the mud window narrows when the deviation exceeds 10° and that the optimum design range for mud weight in vertical wells is between 11.2 and 14.9 ppg. The outcomes of this study can significantly contribute to the understanding of how to analyze the drilling operations and choose the appropriate mud weight parameters to maintain stability and reduce wellbore instability against shaly formations.